(untitled) (Principles and Practice of Clinical Research, 2022)
Introduction: Major depressive disorder (MDD) is a disease with a high economic burden across the world, mainly secondary to a decrease in work performance and pill burden. Ketogenic diet is a type of non-pharmacological intervention that is employed in the treatment of refractory epilepsy and has shown promise for the treatment of other psychiatric disorders, including depression. Up to the date, there is a limited number of investigations regarding this topic, making the knowledge very scarce; therefore, our study will assess the clinical efficacy of ketogenic diet, particularly Modified Atkins Diet, as compared to control diet in adults with diagnostic of MDD on standard treatment without resolution of symptoms as a difference in Montgomery-Åsberg Depression Rating Scale (MADRS) from baseline at the third month follow-up visit. Methods: This is a phase II, multicenter, randomized, controlled, open-label, parallel-group, superiority trial with blinded endpoints. Sample size was calculated as 132 participants (66 participants per arm) to maintain a power of 80% and a two-sided significance level of 0.05. The primary endpoint is the improvement in MDD symptomatology measured by MADRS scale at 3 months from baseline. Discussion: There is evidence to support the notion that ketogenic diet improves patients symptoms by increasing levels of several molecules resulting in a decrease of neuroinflammation and an increase of neurogenesis, improving mood disorders. We hypothesize that a ketogenic diet will improve depressive symptoms in patients with moderate to severe depression when compared to patients on a control diet.